O Expediente: a dimensão esquecida da administração política - Santos, Reinaldo Souza; Barreto, Eduardo Fausto; Ribeiro, Elizabeth Matos; Barreto, Maria da Graça Pitiá (Organizações & Sociedade, 2014)
.